2013
DOI: 10.1007/s00221-013-3721-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-muscle control during bipedal stance: an EMG–EMG analysis approach

Abstract: Posture and postural reactions to mechanical perturbations require the harmonic modulation of the activity of multiple muscles. This precision can become suboptimal in the presence of neuromuscular disorders and result in higher fall risk and associated levels of comorbidity. This study was designed to investigate neurophysiological principles related to the generation and distribution of inputs to skeletal muscles previously recognized as a synergistic group. Specifically, we investigated the current hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
7
28
0
Order By: Relevance
“…Synchronization of EMG signals within this frequency interval (<10 Hz) is consistent with previous studies that reported similar findings during the execution of slow movements (Kamen and DeLuca 1992;Vallbo and Wessberg 1993;Farmer et al 1993;DeLuca and Erim 2002). In fact, similar results have been recently reported by us (Danna-dos-Santos et al 2014). In that study, we reported synchronizations that were not only concentrated between 1 and 10 Hz but also extended to frequencies up to 20 Hz.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Synchronization of EMG signals within this frequency interval (<10 Hz) is consistent with previous studies that reported similar findings during the execution of slow movements (Kamen and DeLuca 1992;Vallbo and Wessberg 1993;Farmer et al 1993;DeLuca and Erim 2002). In fact, similar results have been recently reported by us (Danna-dos-Santos et al 2014). In that study, we reported synchronizations that were not only concentrated between 1 and 10 Hz but also extended to frequencies up to 20 Hz.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we investigated the role of correlated neural inputs as a neural mechanism by which the CNS coordinates the activation of synergistic muscles forming only one of these M-modes (Danna-dos-Santos et al 2014). More specifically, we employed measures of intermuscular coherence between pairs of EMG signals composing the posterior M-mode (soleus, biceps femoris, and lumbar erector spinae muscles) and confirmed the presence of correlated neural inputs to all three muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Intermuscular coherence at higher frequencies has also been reported by several studies. We observed 6–10 Hz intermuscular coherence between leg muscles within and across legs 30 31 . Coherence at 16 Hz has also been observed between leg muscles 30 , in particular in patients with orthostatic tremor in which 16-Hz coherence is very pronounced 32 .…”
Section: Discussionmentioning
confidence: 76%
“…This has relevance to the integration of theories of common drive and motor control supervision. On one hand, coherence reflects common excitatory drive originating from a neural structure (Danna-Dos- Santos et al 2014). At the same time, primary movers in a motor task are closely supervised by the motor control system (Krishnamoorthy et al 2003;Danna-dos-Santos et al 2007).…”
Section: Muscle Contributions Within a Synergymentioning
confidence: 99%
“…Synchronisation within the beta band during precise, steady force outputs of hand muscles have been proposed to be indicative of functional binding between the primary motor cortex and effector muscles (Kilner et al 2000;Boonstra 2009;Danna-Dos Santos et al 2010). Alpha band synchronisation across distinct muscles or even bilateral muscles, as IMC, suggests a common input from subcortical structures (Conway et al 1995;Baker et al 2003) and may specifically reflect the involvement of the reticulospinal pathway (Grosse and Brown 2003) Coherent activity has been described across muscles of an individual synergy during postural responses (Danna-Dos- Santos et al 2014) and a cycling task (Marchis et al 2015).…”
Section: Introductionmentioning
confidence: 99%